ANALISIS YURIDIS TERHADAP PENYELESAIAN SENGKETA KEPEMILIKAN TANAH MELALU JALUR PERADILAN ( STUDI KASUS PENGADILAN NEGERI PARIAMAN ) - Miasiratni Miasiratni; Sri Agustini; Widya Yoseva (Ensiklopedia Research and Community Service Review, 2026)
Abstract: This study aims to examine the process of resolving land ownership disputes through the judicial system at the Pariaman District Court and to identify the obstacles encountered during this resolution process. An empirical legal research method was employed. Data were gathered through interviews with judges and relevant parties at the Pariaman District Court, supplemented by a literature review of laws, regulations, books, and journals concerning land disputes. The data were analyzed qualitatively and presented descriptively. The research findings indicate that the resolution of land ownership disputes at the Pariaman District Court is conducted in accordance with civil procedural law, encompassing the filing of the lawsuit, the mediation process, case examination, the presentation of evidence, and the judicial ruling. In adjudicating cases, judges consider the evidence, witness testimonies, and facts revealed during the proceedings. Obstacles encountered include incomplete land ownership documentation, competing claims from multiple parties regarding the disputed property, and the lengthy evidentiary process. Consequently, there is a need for more organized land administration and increased public awareness regarding the registration of land rights to prevent future disputes.Keywords: Land Ownership Dispute, Dispute Resolution, Pariaman District Court.